Biodiesel Production From Calophyllum Inophyllum Using Base Lewis Catalyst - Lailatul Qadariyah; Donny Satria Bhuana; Raka Selaksa; Ja'far As Shodiq; Mahfud Mahfud (ASEAN Journal of Chemical Engineering, 2018)
The search for renewable alternative energy must be developed, one of which is biodiesel. Seed Calophyllum inophyllum has a fairly high oil content of about 71.4% by weight, has great potential when used as raw material for making biodiesel. The purpose of this research was to synthesize biodiesel from Calophyllum inophyllum oil through the transesterification process using base lewis catalyst with microwave assisted, comparing the performance of sodium acetate to potassium hydroxide, knowing the amount of catalyst required to obtain the best biodiesel, and knowing the optimum power in the manufacture of biodiesel, The first step of making Calophyllum inophyllum biodiesel is degumming process, then continued with esterification. The next process is transesterification, followed by purification of biodiesel. The catalysts used are CH3COONa, and KOH. From the results, Calophyllum inophyllum oil can be used as biodiesel feedstock, the best operating conditions for base catalyst at 300 W power, 1% (w/w) concentration, produced the best yield is 96% (for KOH catalyst) and 87% (for CH3COONa catalyst).